Mies van der Rohe’s Tugendhat House – Weightless Living - Wagner, Monika (Docomomo Journal, 2012)
In his review of Franz Hessel’s "Spazieren in Berlin", Walter Benjamin noted that the author celebrated the "last monuments of an old culture […] for which cosiness came first", but whose time had come. The new architecture transferred "the domicile of men […] into a transit passage of all imaginable forces and waves in light and air. The future stands under the signature of transparency". Two years earlier, Siegfried Kracauer wrote about the exhibition of the Werkbund entitled "Die neue Wohnung" (The New Home) in 1927. Here, the attempt "to undermine the former isolation of the individual by dismantling the external partition walls" became evident. But perhaps "only the anonymous existence of the mass bound to capitalistic economy is granted a voice".